2014
DOI: 10.2151/sola.2014-011
|View full text |Cite
|
Sign up to set email alerts
|

The GOddard SnoW Impurity Module (GOSWIM) for the NASA GEOS-5 Earth System Model: Preliminary Comparisons with Observations in Sapporo, Japan

Abstract: The snow darkening module evaluating dust, black carbon (BC), and organic carbon (OC) depositions on the mass of snow impurities and albedo has been developed for the NASA Goddard Earth Observing System, Version 5 (GEOS-5) Earth System Model, as the GOddard SnoW Impurity Module (GOSWIM). GOSWIM consists of the updated snow albedo scheme from a previous study (Yasunari et al. 2011) and a newly developed mass concentration calculation scheme, directly using aerosol depositions from the chemical transport model (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…The Catchment Land Surface Model [ Ducharne et al ., ; Koster et al ., ] in GEOS‐5 uses the snowpack model of Lynch‐Stieglitz [], and GOSWIM follows the constituent tracers through each of the snow model's three layers (see Figure 1 of Yasunari et al . []). We perform two sets of simulations, one with dust, BC, and OC constituents in snow and one without them; we then compare these sets of simulations to quantify the impact of the constituents on boreal spring climate (see the descriptions mentioned later).…”
Section: Methods and Datamentioning
confidence: 99%
See 3 more Smart Citations
“…The Catchment Land Surface Model [ Ducharne et al ., ; Koster et al ., ] in GEOS‐5 uses the snowpack model of Lynch‐Stieglitz [], and GOSWIM follows the constituent tracers through each of the snow model's three layers (see Figure 1 of Yasunari et al . []). We perform two sets of simulations, one with dust, BC, and OC constituents in snow and one without them; we then compare these sets of simulations to quantify the impact of the constituents on boreal spring climate (see the descriptions mentioned later).…”
Section: Methods and Datamentioning
confidence: 99%
“…The 32 deposition variables from GOCART included wind‐generated dust, BC from anthropogenic and natural sources including fossil fuel and biomass burning, and OC from the BC sources and from biogenic emission, sent to the snow surface through dry deposition, large‐scale and convective scavenging (wet), and gravity sedimentation (dust only) [ Chin et al ., , ; Ginoux et al ., ; Colarco et al ., ]; also, see some descriptions on the used emission data in Yasunari et al . [, and references therein]. Once deposited on the snow surface, the nine constituent tracers are followed through the snow using GOSWIM [ Yasunari et al ., ], as discussed below.…”
Section: Methods and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Chýlek et al, 1983;Warren, 1984;Clarke and Noone, 1985;Warren and Clarke, 1990;Grenfell et al, 2002;Lee Taylor and Madronich, 2002;Jacobson, 2004;Flanner et al, 2007;Doherty et al, 2010;Reay et al, 2012;Ye et al, 2012;King, 2013, 2014). Field observations and modelling simulations have also shown that increases in dust deposition to snow lead to radiative forcing that affects the energy balance of snow (Woo and Dubreuil, 1985;Aoki et al, 1998;Painter et al, 2007Painter et al, , 2012Huang et al, 2011;Wang et al, 2013;Zhang et al, 2013;Zhao et al, 2014;Yasunari et al, 2014). However, although anthropogenic deposits in polar snow and ice have been well characterised, studies on the effects of natural mineral aerosol deposits are more scarce.…”
Section: L Lamare Et Al: Mineral Aerosol Deposits On Sea Icementioning
confidence: 99%